Mass spectrometric characterization of glycosylation of Hepatitis C virus E2 envelope glycoprotein reveals extended microheterogeneity of N-glycans - Iacob, Roxana E. (2007)
Hepatitis C virus (HCV) causes acute and chronic liver disease in humans, including chronic hepatitis, cirrhosis, and hepatocellular carcinoma. The polyprotein encoded in the HCV genome is co- and posttranslationally processed by host and viral peptidases, generating the structural proteins Core, E1, E2 and p7, and five non-structural proteins. The two envelope proteins E1 and E2 are heavily glycosylated. Studying the glycan moieties attached to the envelope E2 glycoprotein is important because the N-linked glycans on E2 envelope protein are involved in the interaction with some human neutralizing antibodies, and may also have a direct or indirect effect on protein folding. In the present study we report the mass spectrometric characterization of the glycan moieties attached to the E2 glycoprotein. The mass spectrometric analysis clearly identified the nature, composition and microheterogeneity of the sugars attached to the E2 glycopeptides. All 11 sites of glycosylation on E2 protein were characterized, and the majority of these sites proved to be occupied by high mannose glycans. However, complex type oligosaccharides, which have not been previously identified, were exclusively observed at two N-linked sites and their identity and heterogeneity were determined.